Synergistic Effect of Blast Furnace Slag and Fly Ash on the Properties of Polyamide 6 - Akkoyun Kurtlu, Meral; Tuna, Sibel (Wiley, 2026)
The use of waste products such as ground-granulated blast furnace slag (BFS) and fly ash (FA) as fillers in polymer matrices is a relatively new approach. Polymer composites prepared with BFS and FA can be suitable candidates for applications requiring electrical insulation properties due to their improved mechanical properties, wear resistance, and thermal resistance, as well as their low electrical conductivity. The aim of this work is to investigate the synergistic effects of BFS and FA on the final structural, thermal, mechanical, morphological, and electrical conductivity properties of polyamide 6 (PA6), a thermoplastic polymer widely used in the plastic industry. When BFS/FA-added PA6 composites prepared at ratios of 5, 10, 20, 30, and 40 wt.% using twin screw extruder and compression molding methods were characterized, the physical interactions were observed at the intermolecular level. A general decrease in tensile strength values with increasing BFS/FA content was obtained. BFS/FA particles were homogeneously dispersed in the PA6 matrix, but a weak interaction occurs at the filler-matrix interface. Concerning the electrical conductivity results, the use of BFS/FA fillers in PA6 composites improved the electrical conductivity values as intended, but the interfacial compatibility should be increased in applications requiring mechanical performance.
Keywords: composites; extrusion; mechanical properties; polyamides; recycling